Immune response following traumatic spinal cord injury: Pathophysiology and therapies - Sterner, Robert C.; Sterner, Rosalie M. (Frontiers in Immunology, 2023)
Traumatic spinal cord injury (SCI) is a devastating condition that is often associated with significant loss of function and/or permanent disability. The pathophysiology of SCI is complex and occurs in two phases. First, the mechanical damage from the trauma causes immediate acute cell dysfunction and cell death. Then, secondary mechanisms of injury further propagate the cell dysfunction and cell death over the course of days, weeks, or even months. Among the secondary injury mechanisms, inflammation has been shown to be a key determinant of the secondary injury severity and significantly worsens cell death and functional outcomes. Thus, in addition to surgical management of SCI, selectively targeting the immune response following SCI could substantially decrease the progression of secondary injury and improve patient outcomes. In order to develop such therapies, a detailed molecular understanding of the timing of the immune response following SCI is necessary. Recently, several studies have mapped the cytokine/chemokine and cell proliferation patterns following SCI. In this review, we examine the immune response underlying the pathophysiology of SCI and assess both current and future therapies including pharmaceutical therapies, stem cell therapy, and the exciting potential of extracellular vesicle therapy.